Unionism in Canada and the United States in the 21st Century: The Prospects for Revival - Rose, Joseph; Chaison, Gary (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles, 2001)
SummaryBased on a review and comparison of recent developments in organizing, collective bargaining and political action, this paper considers the potential for union revival in Canada and the United States. Although unions have devoted considerable energy and resources to new initiatives, the overall evidence leads us to generally pessimistic conclusions. The level and direction of union density rates indicates the two labour movements lack the institutional frameworks and public policies to achieve sustained revival. Significant gains in union membership and density levels will require nothing less than a paradigm shift in the industrial relations systems—a broadening of the scope and depth of membership recruitment, workplace representation and political activities.